Effect of Zumba Fitness Programme on Skinfold Measurement and Body Weight in Females of Keshar Apartments, Gwalior: The Effectiveness of Zumba Fitness Programme for Skinfold Measurement and Body Weight in Females (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The aim of this research was to determine the effects of Zumba Fitness Programme on Skinfold Measurement and Body Weight in Females of Keshar Aprtment, Gwalior. Twenty females aged 25-35 participated in the research. The Zumba Fitness Programme was scheduled for eight weeks of exercise, total 40 training sessions. Triceps, subscapular, abdomen and thigh four sites were chosen for skin fold measurement. Training effect was also seen in body weight. The selected skinfold sites and body weight were measured at the beginning and at the end of the research. The effects of Zumba training were analyzed by using one sample T test. The obtained result showed that Zumba fitness programme achieved statistically significant improvement in abdomen (p=.048) and body weight (p=0.021). The increased values of triceps (p=1), subscapular (p=.931), thigh (p=.351) were not statistically significant. The study results clearly indicated that the Zumba fitness exercise can be used as effective group fitness exercise for body weight reduction and abdomen skinfold of women.